EFFECT OF REARRANGEMENTS OF HOMOEOLOGOUS GROUP 2 CHROMOSOMES OF BREAD WHEAT ON SPIKE MORPHOLOGY - O. B. Dobrovol’skaya; P. Martinek; I. G. Adonina; E. D. Badaeva; Yu. L. Orlov; E. A. Salina; L. I. Laikova (Вавиловский журнал генетики и селекции, 2015)
Four genetically independent bread wheat lines with altered spike morphology caused by development of supernumerary spikelets at rachis nodes were characterized by modern methods of karyotype analysis, Cbanding and FISH. Three lines carried rearrangements of group 2 chromosomes: substitution of chromosome 2D and deletions of 2D, terminal and interstitial. The deletion breakpoints were defined by microsatellite analysis. The deletions were co-localized on the genetic map with the MRS1 gene, whose mutation caused the development of clusters of supernumerary spikelets at rachis nodes. Evaluations of spike phenotypes of the line with the supernumerary spikelet trait and Chinese Spring deletion lines carrying deletions of chromosomes 2A, 2B, and 2D demonstrated that deletion of a group 2 chromosome might alter spike morphology, resulting in development of supernumerary spikelets at rachis nodes and changes in spike length and density.